2013
DOI: 10.1186/2193-1801-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary flaxseed oil level on the growth performance and fatty acid composition of fingerlings of rainbow trout, Oncorhynchus mykiss

Abstract: This study evaluated the suitability of flaxseed oil as a source of supplemental dietary lipid for fingerlings of rainbow trout (Oncorhynchus mykiss). Triplicate groups of the 30 fingerlings held under identical culture conditions were fed twice daily by iso-nitrogenous, iso-calorific and iso-lipidic diets for 8 weeks. Experimental diets consisted of 30.2% protein, 18.6 kJ g -1 energy and 16.5% lipid from fish oil (FO), flaxseed oil (FxO) and 1:1 blends of the oils (FFxO). Moisture, ash, protein, final body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
270
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(284 citation statements)
references
References 42 publications
13
270
1
Order By: Relevance
“…This is reflected in the fish tissues. Previous studies have reported that the percentages of EPA and DHA were higher in fish fed with the fish oil diet, compared with vegetable oil diets (Aminikhoei et al 2013;Masiha, Ebrahimi, Soofiani & Kadivar, 2013). In our study, it was determined that EPA (20:5n-3) and DHA (22:6n-3) levels in the tissues (muscle and liver) of fish fed with fish oil were higher than those fed with vegetable oil diets.…”
Section: Discussionsupporting
confidence: 49%
“…This is reflected in the fish tissues. Previous studies have reported that the percentages of EPA and DHA were higher in fish fed with the fish oil diet, compared with vegetable oil diets (Aminikhoei et al 2013;Masiha, Ebrahimi, Soofiani & Kadivar, 2013). In our study, it was determined that EPA (20:5n-3) and DHA (22:6n-3) levels in the tissues (muscle and liver) of fish fed with fish oil were higher than those fed with vegetable oil diets.…”
Section: Discussionsupporting
confidence: 49%
“…The authors of this study found that the QAPFS was longer for gefitinib than for the doublet chemotherapies, confirming the progression-free survival benefit of first-line gefitinib in advanced NSCLC EGFR M + patients over standard care. Another study evaluated trade-offs between QoL and survival improvement, in terms of quality-adjusted survival outcomes, by comparing patients with advanced breast cancer treated with single-agent mitoxantrone and combination of cyclophosphamide, methotrexate, 5-fluorouracil, and prednisone (CMFP) [13]. In that study, QAPFS for each group was the product of its mean utility score and the area under its time-to-progression curve truncated at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment and performance of these microorganisms in the field can be affected by numerous environmental variables, such as soil pH, salinity, moisture content, and temperature [19]. Despite these limitations, continuing research may enable more widespread use of these biofertilizers.…”
Section: Plant Growth Promotionmentioning
confidence: 99%